Assessing the knowledge, attitudes and barriers regarding health promotion of breast cancer among community pharmacists - Muna Oqal; Mohanad Odeh; Rawan Abudalu; Abdelrahim Alqudah; Roaa Alnajjar; Yazeed Bani Younes; Maram Al-Shawabkeh; Luma Taha (Future Science OA, 2022)
Aim: This study aimed to identify the perspective knowledge, attitudes, and barriers of community pharmacists in promoting breast cancer health. Methods: An internet-based self-administrated questionnaire was distributed using social media groups to the community pharmacists in Jordan. Results: A 76.7% of the pharmacists had insufficient knowledge score of breast cancer and 92.7% had positive attitude. Access to breast cancer educational materials was the major barrier to pharmacists. A significant association was found between pharmacists' knowledge and breast cancer educational materials being given to patients (p < 0.001). Conclusion: Despite the low breast cancer knowledge score and stated barriers that could prevent actualizing community pharmacists' role, they had positive attitude toward educating patients about breast cancer health.